„minden perc, minden papir pénz”: A jogi és gazdasági diskurzus összjátéka Kosztolányi Dezső első kötetének alakulásában - Zákány Tóth, Péter (Studia Litteraria, 2018)
The paper aims to answer the question how legal and economic environment shapes literary oeuvres. The possible impact is investigated in the relationship of the first and second editions of Within Four Walls (Négy fal között), Dezső Kosztolányi’s first collection of poems. The importance of this interrelation can be opposed to Ady’s oft-quoted criticism, “Kosztolányi is a literary author.” If the reason behind Kosztolányi being compelled to radically rearrange the second edition of his book was that the first edition was basically not self-published, then the economic environment of literary works cannot only be considered an implicit and unspoken factor of the autonomy of literature but a condition having direct influence on literary compositions.